2018
DOI: 10.1002/jsfa.9447
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the content of anthocyanins, flavonols, and antioxidant activity in Fragaria ananassa var. Camarosa fruits under traditional and organic fertilization

Abstract: BACKGROUND: Strawberries are consumed worldwide. In Chile, strawberry production has been established in Andisols, were phosphorus is scarce. Traditional fertilization (TF) and organic fertilization (OF) have both been established there. This study examined their impact on the polyphenolic content of strawberries. RESULTS: Two anthocyanins were identified by high performance liquid chromatography with diode array detection coupled to mass spectrometry (HPLC-DAD-ESI-MS/MS). The average total anthocyanin concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
1
17
2
Order By: Relevance
“…The profile of the anthocyanins measured was matching (concordant) with previous results obtained by Ruiz et al (2019), in which mainly pelargonidin derivatives and pelargonidin-3-glucoside as the most abundant compound were detected. Anthocyanin concentrations results were in contrast to Fertilisation treatments: OF, organic fertilisation; TF, chemical fertiliser; WF, without fertilisation and doses 50% or 100% of the recommended fertilisation those of Carvajal et al (2012), where the highest concentrations of anthocyanins in Camarosa strawberry cultivar were obtained in treatments with lower levels of organic matter and higher levels of nutrient supplied, suggesting that higher concentrations of P alone may not significantly influence the concentrations of anthocyanins in the berries.…”
Section: Phenolic Compounds and Antioxidant Activity In Strawberry Frsupporting
confidence: 90%
See 2 more Smart Citations
“…The profile of the anthocyanins measured was matching (concordant) with previous results obtained by Ruiz et al (2019), in which mainly pelargonidin derivatives and pelargonidin-3-glucoside as the most abundant compound were detected. Anthocyanin concentrations results were in contrast to Fertilisation treatments: OF, organic fertilisation; TF, chemical fertiliser; WF, without fertilisation and doses 50% or 100% of the recommended fertilisation those of Carvajal et al (2012), where the highest concentrations of anthocyanins in Camarosa strawberry cultivar were obtained in treatments with lower levels of organic matter and higher levels of nutrient supplied, suggesting that higher concentrations of P alone may not significantly influence the concentrations of anthocyanins in the berries.…”
Section: Phenolic Compounds and Antioxidant Activity In Strawberry Frsupporting
confidence: 90%
“…Phenolic compound determinations from strawberry fruits were performed according to Parada et al (2019), whereas ascorbic acid was determined based on the reported by Ruiz et al (2019). Chromatographic analyses were carried out on an HPLC-DAD Shimadzu (Tokyo, Japan) equipped with a quaternary pump LC-20AT, a DGU-20A5R degasser unit, a CTO-20A oven and a UV-Vis diode array detector (SPDM20A).…”
Section: Extraction and Quantification Of Non-enzymatic Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic composition of root organs (mainly rhizomes) from I. cylindrica has been previously reported where mainly flavones were detected [ 38 ]; however, only p-coumaric acid and tricin have been previously reported in shoots [ 20 ]. It is noticeable that phenolic compounds as anthocyanins or hydroxycinnamic acids are main responsible of the antioxidant activity [ 39 ], also playing an important role in the protection of tissues to cope with the damage induced by ROS. As previously mentioned, here we identified six signals of phenolic compounds; however, according to the reported by Yang et al [ 40 ], the other not-identified metabolites corresponded to flavonoid glycosydes (subtypes of flavonoid O-glycosides, detected in peaks 6 , 8 , 9A , 9B and 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some phenolic compounds are very photosensitive, as a result, rapid extraction methods are necessary to avoid the degradation of them [28]. Liquid-liquid extraction (LLE) and solid-liquid extraction (SLE) followed by a stage of concentration and purification are the most widely used methods to make a selective extraction of phenolic compounds from various matrices [2,3,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%